Study of biochemical and oxidative stress markers in the first-degree relatives of persons with type 2 diabetes stratified by glucose tolerance test - Yadav, Dhananjay; Mishra, Meerambika; Rana, Seema; Subramani, Senthil K; Prasad, GBKS (Progress in Nutrition, 2017)
Background and Aim: The present study has been attempted to compare the relative tolerance to glucose in first-degree relatives of type 2 diabetic patients and estimate the anthropometric, biochemical parameters and markers of oxidative stress in subjects with the different degree of glucose tolerance. Methodology: The study consisted of 34 subjects aged between 20-45 years, with established family history of type 2 diabetes mellitus, who were subjected to oral glucose tolerance test (OGTT). Those without any family history of diabetes served as controls. Results: Out of the 34 subjects, 5 subjects exhibited high tolerance, 18 showed a moderate degree of glucose tolerance and 9 subjects were with low glucose tolerance. Only 2 subjects were categorized as highly intolerant after OGTT. In almost all subjects with glucose tolerance test, the peak plasma glucose level was recorded at 60 minutes after oral glucose administration. In the present study subjects, with a high degree of glucose intolerance showed significantly higher levels of triglyceride (171±9.8**) mg/dl and VLDL levels (34.2±1.9**) mg/dl. A significant increase in the TBARS levels (2.9±0.053**) µg/ml was recorded in subjects with a high degree of glucose intolerance. A corresponding decrease in the reduced glutathione (1.6±2.2) mg/ml and superoxide dismutase activity (0.7±0.08) units/min/mg protein was also recorded. Conclusion: The study revealed disturbance in the lipid parameters and antioxidant defenses in the first degree relative of diabetic patients even before the establishment of disease.